ANALISIS PENGARUH KONSUMSI DAN DISTRIBUSI TERHADAP PRODUKSI KOPI ARABIKA DI DESA SINAMAN II KECAMATAN PAMATANG SIDAMANIK KABUPATEN SIMALUNGUN - Rizal Paruhuman Lubis; Rika Novita Sari Manik (Bisnis-Net, 2023)
Arabica coffee is considered superior to Robusta due to its taste and quantity and is also low in caffeine. The variables of this study include Arabica coffee production with variable Y, consumers and distribution as variable X in Sinaman II Village, Pamatang Sidamanik district, Simalungun Regency using multiple linear regression methods. The data obtained from distributing the questionnaires were processed using SPSS software Version 24.0 For Windows. The purpose of this study was to analyze and find out which factors (consumption and distribution) significantly influence Arabica coffee production in Sinaman II Village. The results of the study Consumption and distribution have a positive and significant influence on arabica coffee production in Sinaman II Village, Pamatang Sidamanik District, Simalungun Regency. The coefficient of determination shows the adjusted R Square number of 0.725 which can be called the coefficient of determination which in this case means that 72.5% of Arabica coffee production in Sinaman II Village can be obtained and explained by Consumption and Distribution. While the remaining 100% - 72.5% = 27.5% is influenced by other variables that are not included in the model or not examined.